Bentuk-Bentuk Disfemisme pada Akun Instagram @kpipusat dan Implementasinya sebagai Bahan Ajar Bahasa Indonesia di SMA - Sutanto, Dwi; Assidik, Gallant Karunia (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
The freedom to comment on social media allows netizens to freely comment. The purpose of this research is to describe the forms and functions of dysphemism in the comments of the Instagram account @kpipusat and its implementation is used as Indonesian language learning material at the high school level. This research is a qualitative descriptive study. The data in this study are expressions of dysphemism in the comments of the Instagram account @kpipusat. The data collection method used in this study is the listening method with advanced techniques, free listening, conversation, and note-taking techniques. The data analysis method used the distribution method with the advanced BUL technique (Bagi Unsur Langsung) and the matching method with advanced techniques. The results of this study indicate that the data found in the form and function of dysphemism. The forms of dysphemism in the comments column of the Instagram account @kpipusat are in the form of words, clauses and sentences. Meanwhile, the functions found are in the form of ridicule (insulting, insinuating, or dropping), the function of expressing annoyance, the function of showing disapproval, and the function of showing a negative image of someone or something.